PEMETAAN POTENSI DAERAH BERDASARKAN PRODUK DOMESTIK REGIONAL BRUTO MENGGUNAKAN METODE TIPOLOGI KLASSEN DAN LOCATION QUETIENT ( LQ ) (STUDI KASUS DI KABUPATEN REMBANG TAHUN 2016-2020) - Wahyuningsih, Panca; Wicaksono, Taufik (JAB (Jurnal Akuntansi & Bisnis), 2021)
Rembang Regency, one of the regencies in Central Java province, has various potentials that can be developed to support regional development. This study aims to determine the sectors that can become prime sectors in Rembang Regency.This study uses secondary data from the Central Bureau of Statistics of Rembang Regency in the form of Gross Regional Domestic Income (GRDP) of Rembang Regency from 2016 to 2020. Gross Regional Domestic Product (GRDP) is the number of goods and services produced by all people in one place during a certain period of time. . There are 2 kinds of GRDP, namely GRDP at current prices and constant prices. Here the researcher uses GRDP at current prices for that year and uses the production method, meaning how many goods and services are produced from the sector.By using the Klassen Typology method, it can be seen which sectors are prime, potential, developing and underdeveloped sectors in Rembang Regency. From the results of the analysis conducted by the researchers,it was found that the manufacturing sector and the construction sector were the prime sectors in Rembang Regency.Keywords: GRDP, Klassen Typology, Location Quetient (LQ), Rembang Regency